2021
DOI: 10.20525/ijrbs.v10i4.1165
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human resources (HR) activities on competitive advantage in private schools in Jordan

Abstract: The aim of this study was to identify the impact of HR activities on competitive advantage in private schools. The study uses primary data collected with the help of a well-structured questionnaire that was developed and distributed among a sample of 92 respondents (49 female and 43 male), questionnaire results were statistically analyzed to test the hypotheses that were developed to identify the impact of HR activities on competitive advantages. Multiple regression analysis was used as a statistical tool and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…According to the calculation process of formula (3), several relatively suitable personnel are matched for each posi-tion. Due to the limited number of personnel required for each post, it is necessary to allocate human resources for enterprise posts in descending order according to the number of personnel required by the post and the level of personnel excellence [18,19]. Therefore, select local efficiency P p ðiÞ and predict the work efficiency of the person in the post according to the calculation result of formula (1); then,…”
Section: Matching Personnel and Positions Based On Intelligentmentioning
confidence: 99%
“…According to the calculation process of formula (3), several relatively suitable personnel are matched for each posi-tion. Due to the limited number of personnel required for each post, it is necessary to allocate human resources for enterprise posts in descending order according to the number of personnel required by the post and the level of personnel excellence [18,19]. Therefore, select local efficiency P p ðiÞ and predict the work efficiency of the person in the post according to the calculation result of formula (1); then,…”
Section: Matching Personnel and Positions Based On Intelligentmentioning
confidence: 99%
“…That is why there is a need for human resource management. The effectiveness of human resource management in schools is vital; the primary key to planning and educational development programs to run optimally is in the hands of educators and education staff in schools (Gunawan, 2021;Ahmad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regression analysis as a statistical method and methodology allowed for the identification of five important factors: hiring and compensation systems, training and skill development activities, organisational climate, employee engagement, and decentralisation; and the establishment of an efficient communication system that provides a competitive advantage for private schools in Jordan. The study found that HR activities had a statistically significant impact on a firm's competitive advantage [2]. In order to clarify the role of HRD as a dependent variable, Mohammed A A adopted an exploratory and analytical approach in conducting this study.…”
Section: Introductionmentioning
confidence: 99%
“…s material consumption is different. The above is the detailed information on the material consumption table of the employees participating in the experiment (No [1][2][3][4][5][6][7][8][9][10][11][12],. as shown in Table…”
mentioning
confidence: 99%